Kynurenine is the main metabolite of tryptophan degradation by tryptophan 2,3-dioxygenase in HepG2 tumor cells - Oweira, Hani; Lahdou, Imad; Mehrle, Stefan; Khajeh, Elias; Nikbakhsh, Rajan; Ghamarnejad, Omid; Terness, Peter; Reißfelder, Christoph; Sadeghi, Mahmoud; Ramouz, Ali (Journal of Clinical Medicine, 2022)
There are two main enzymes that convert tryptophan (Trp) to kynurenine (Kyn): tryptophan-2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO). Kyn accumulation can promote immunosuppression in certain cancers. In this study, we investigated Trp degradation to Kyn by IDO and TDO in primary human hepatocytes (PHH) and tumoral HepG2 cells. To quantify Trp-degradation and Kyn-accumulation, using reversed-phase high-pressure liquid chromatography, the levels of Trp and Kyn were determined in the culture media of PHH and HepG2 cells. The role of IDO in Trp metabolism was investigated by activating IDO with IFN-γ and inhibiting IDO with 1-methyl-tryptophan (1-DL-MT). The role of TDO was investigated using one of two TDO inhibitors: 680C91 or LM10. Real-time PCR was used to measure TDO and IDO expression. Trp was degraded in both PHH and HepG2 cells, but degradation was higher in PHH cells. However, Kyn accumulation was higher in the supernatants of HepG2 cells. Stimulating IDO with IFN-γ did not significantly affect Trp degradation and Kyn accumulation, even though it strongly upregulated IDO expression. Inhibiting IDO with 1-DL-MT also had no effect on Trp degradation. In contrast, inhibiting TDO with 680C91 or LM10 significantly reduced Trp degradation. The expression of TDO but not of IDO correlated positively with Kyn accumulation in the HepG2 cell culture media. Furthermore, TDO degraded L-Trp but not D-Trp in HepG2 cells. Kyn is the main metabolite of Trp degradation by TDO in HepG2 cells. The accumulation of Kyn in HepG2 cells could be a key mechanism for tumor immune resistance. Two TDO inhibitors, 680C91 and LM10, could be useful in immunotherapy for liver cancers.
Gesehen am 13.09.2022